Comparison among factors - Autonomy, Attitude, and managerial support for job satisfaction in IT organization teleworking environment during COVID 19 – Research in India - Shah, Nidhi Narendrakumar (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management